Development of the website for searching personnel post in Nakhon Pathom Rajabhat University. - Inyaem, Kanya (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
The objectives of this study is develop a website for easily searching a personnel letter of Nakhon Pathom Rajabhat University and evaluating satisfaction from users . This training program is tested with a sample group of 285 which are professors and officers. The research instrument is a questionnaire. Statistic in this research used the percentage and mean The findings of this research were as follows : Users are satisfied with development website searching personnel letter of Nakhon Pathom Rajabhat University includes the innovation and the operating system at appropriate level (Mean = 3.74) In very high level. Article history : Received 11 April 2018 Revised 1 May 2018 Accepted 7 May 2018 SIMILARITY INDEX = 0.00